Analysis of the Effect of Renewable Energy Consumption and Industrial Production on CO2 Emissions in Turkic Republics by Panel Data Analysis Method - Yesbolova, Ainur Yergazievna; Abdulova, Tolkyn; Nurgabylov, Murat; Yessenbekova, Sapargul; Turalina, Svetlana; Baytaeva, Gulnara; Myrzabekkyzy, Kundyz (International Journal of Energy Economics and Policy, 2024)
This study aims to analyze the impact of energy consumption and industrial production on CO2 emissions in the Turkic Republics using the Panel Data method for the period 2000-2020. However, Turkmenistan was excluded from the analysis because the relevant data could not be accessed. Data from Kazakhstan, Azerbaijan, Kyrgyzstan, and Uzbekistan were analyzed. CO2 emission creates problems in terms of environment and sustainability and is a parameter that all countries and international organizations carefully monitor and try to reduce. Using panel data regression, this study examined whether renewable energy and industrial production and countries impact CO2 emissions. The findings revealed that as renewable energy consumption increases, CO2 emissions decrease. However, the effect of industrial production on CO2 emissions was not statistically significant. These results demonstrate that the industrial development of selected countries does not pose a CO2 emission problem. A comparison of countries showed that the high CO2 emission value for Kazakhstan was also reflected in the panel data regression findings, and among the four countries, the country effect was positive only for Kazakhstan. This study is noteworthy in revealing the effect of renewable energy consumption on CO2 emissions. To reduce CO2 emissions and gain a better understanding of the impact of renewable energy consumption on CO2 emissions, future studies should include both developing countries and OECD countries, and compare the results obtained from them.